PENGARUH MODAL PSIKOLOGI DAN PERAN KETERLIBATAN KARYAWAN TERHADAP KINERJA PEGAWAI DENGAN MEDIASI KOMITMEN ORGANISASIONAL (STUDI PADA LEMBAGA PENJAMINAN MUTU PENDIDIKAN PROVINSI JAWA TENGAH) - Padmi Meilia, Christina Hendri; Setyowati, Widhy (Jurnal Ilmiah Telaah Manajemen, 2016)
The performance of LPMP employees, especially the public servants, is not optimum and tends to decrease. This situation leads to poor organizational commitment and performances. This is a case study conducted at LPMP Provinsi Jawa Tengah. The purposes of the study are to identify the influence of psychological capital, and employee engagement on the employee’s performance. The mediating variable of this study is organizational commitment. Employing population technique, 135 public servants of LPMP are involved in the study. The instrument is examined through factor analysis, i.e. validity and reliability tests. To analyze the data the multiple linear regressions is used by employing determination coefficient model and F-test, and also conducting t-test to examine the hypothesis. The analysis reveals the following results; psychological capital has positive significant influence on organizational commitment, and employee engagement influences positively and significantly towards organizational commitment, psychological capital and employee engagement affect on employee’s performance positively and significantly, organizational commitment does not mediate on employee’s performance. The most dominant variable influencing organizational commitment is employee engagement, and the most dominant variable affecting employee’s performance is employee engagement. Key words : psychological capital, employee engagement, organizational commitment, employee’s performance